2019
DOI: 10.1167/iovs.18-25694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trabeculectomy on Waveform Changes of Laser Speckle Flowgraphy in Open Angle Glaucoma

Abstract: PURPOSE.To investigate the effect of trabeculectomy on the waveform changes of laser speckle flowgraphy (LSFG) in the optic nerve head (ONH) in patients with glaucoma.METHODS. Forty-eight eyes of 48 patients with open angle glaucoma were included in this prospective study. LSFG was performed before and 1, 3, and 6 months after trabeculectomy. Longitudinal changes in average mean blur rate (MBR), blow out score (BOS), resistivity index (RI), falling rate, skew, acceleration time index, and blow out time in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…In 48 eyes with open-angle glaucoma, Takeshima et al13 found that BOS increased and RI decreased following trabeculectomy, with no accompanying change in average MBR. Similarly, in our study, as seen in Table 2, BOS was significantly higher in normal control eyes than in the P3 eyes without functional loss, with P = 0.039, while RI was lower in the normal control eyes, although with P = 0.058.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 48 eyes with open-angle glaucoma, Takeshima et al13 found that BOS increased and RI decreased following trabeculectomy, with no accompanying change in average MBR. Similarly, in our study, as seen in Table 2, BOS was significantly higher in normal control eyes than in the P3 eyes without functional loss, with P = 0.039, while RI was lower in the normal control eyes, although with P = 0.058.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is able to parameterize and hence quantify aspects of the pulsatile waveform, potentially revealing insights into pathophysiological changes in the response across the cardiac cycle. Though the physiological specifications of these parameters have not been systemically investigated, multiple studies have shown they can be used to reveal hemodynamic differences in glaucoma 10,1315. This suggests that LSFG may provide a way to assess and quantify changes in both ONH blood flow and its pulsatile variation in vivo in human glaucoma.…”
mentioning
confidence: 99%
“…RI demonstrated a significant decrease over time in all regions. An open-angle glaucoma study, in a young age group reported that, BOS increased with a decrease in RI, suggesting maintenance of stable blood flow 25 . As shown by the waveform area illustrated in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The MBR images of the ONH were recorded at a rate of 30 frames/s over a 4 s period and automatically detected the beginning and the end of the heartbeat recorded within 4 s. The total number of frames was 118 (Figure 1(b)). Images corresponding to the identical phases within 1 heartbeat duration were synthesized to one image sequence [27]. The averaged MBR for a heartbeat was calculated and displayed as a heartbeat map (Figure 1(c)).…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed that the skew and blowout time (BOT) correlated with the mean deviation (MD) in patients with primary open-angle glaucoma (POAG) [26]. However, to the best of our knowledge, only one trabeculectomy study [27] has performed pulse waveform analysis of ocular blood flow before and after glaucoma treatment. The purpose of the present study was to evaluate the effect of PG analog instillation or trabeculectomy on the pulse waveforms for ONH microcirculation using LSFG.…”
Section: Introductionmentioning
confidence: 99%